Data of a stiffness softening mechanism effect on proliferation and differentiation of a human bone marrow derived mesenchymal stem cell line towards the chondrogenic and osteogenic lineages - Linxiao Wu; Adrián Magaz; Tao Wang; Chaozong Liu; Arnold Darbyshire; Marilena Loizidou; Mark Emberton; Martin Birchall; Wenhui Song (Data in Brief, 2018)
This article contains data related to the research article entitled “Stiffness memory of indirectly 3D-printed elastomer nanohybrid regulates chondrogenesis and osteogenesis of human mesenchymal stem cells” [1] (Wu et al., 2018).Cells respond to the local microenvironment in a context dependent fashion and a continuous challenge is to provide a living construct that can adapt to the viscoelasticity changes of surrounding tissues. Several materials are attractive candidates to be used in tissue engineering, but conventional manufactured scaffolds are primarily static models with well-defined and stable stiffness that lack the dynamic biological nature required to undergo changes in substrate elasticity decisive in several cellular processes key during tissue development and wound healing. A family of poly (urea-urethane) (PUU) elastomeric nanohybrid scaffolds (PUU-POSS) with thermoresponsive mechanical properties that soften by reverse self-assembling at body temperature had been developed through a 3D thermal induced phase transition process (3D-TIPS) at various thermal conditions: cryo-coagulation (CC), cryo-coagulation and heating (CC + H) and room temperature coagulation and heating (RTC + H). The stiffness relaxation and stiffness softening of these scaffolds suggest regulatory effects in proliferation and differentiation of human bone-marrow derived mesenchymal stem cells (hBM-MSCs) towards the chondrogenic and osteogenic lineages.